1996
DOI: 10.1126/science.272.5260.398
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Brassinosteroids in Light-Dependent Development of Arabidopsis

Abstract: Although steroid hormones are important for animal development, the physiological role of plant steroids is unknown. The Arabidopsis DET2 gene encodes a protein that shares significant sequence identity with mammalian steroid 5 alpha-reductases. A mutation of glutamate 204, which is absolutely required for the activity of human steroid reductase, abolishes the in vivo activity of DET2 and leads to defects in light-regulated development that can be ameliorated by application of a plant steroid, brassinolide. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
611
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 812 publications
(633 citation statements)
references
References 19 publications
18
611
0
4
Order By: Relevance
“…Firstly, the Y610F plants had dramatically reduced responses to exogenous brassinolide (BL) in terms of two well recognized physiological read-outs of BR signaling: (1) hypocotyl elongation 2,33,34 and (2) dephosphorylation of BES1. 35,36 The former observation is also apparent in the reduced hypocotyl lengths of seedlings grown in the absence of exogenous BL, with Y610F plants having the shortest hypocotyls, followed by Y610E plants and wild type BAK1-Flag plants (Fig. 2 and reviewed in ref.…”
Section: Bak1 Is a Dual-specificity Kinasementioning
confidence: 88%
“…Firstly, the Y610F plants had dramatically reduced responses to exogenous brassinolide (BL) in terms of two well recognized physiological read-outs of BR signaling: (1) hypocotyl elongation 2,33,34 and (2) dephosphorylation of BES1. 35,36 The former observation is also apparent in the reduced hypocotyl lengths of seedlings grown in the absence of exogenous BL, with Y610F plants having the shortest hypocotyls, followed by Y610E plants and wild type BAK1-Flag plants (Fig. 2 and reviewed in ref.…”
Section: Bak1 Is a Dual-specificity Kinasementioning
confidence: 88%
“…Physiological studies have demonstrated that BR can induce diverse cellular responses such as stem elongation, pollen tube growth, leaf bending and epinasty, root inhibition, induction of ethylene biosynthesis and fruit ripening, and xylem differentiation [3][4][5][6]. The identification of Arabidopsis BR biosynthetic mutants established that BR is a new class of phytohormone with an essential role in plant growth and development [7][8][9]. Since then, extensive molecular genetic and biochemical studies of BR signaling in Arabidopsis thaliana have illustrated a BR signal transduction pathway from ligand perception on the cell surface to gene expression in the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…66,83 On the contrary, overexpression of the TCP1SRDX chimeric repressor gene in wild type plants leads to dwarfed transgenic plants resembling typical BR-deficient or -insensitive mutants. 66,84 DWARF4 (DWF4) codes for a 22-hydroxylase and is responsible for multiple 22-hydroxylation steps during BR biosynthesis. 85 Combined with real-time RT-PCR analysis and chromatin immunoprecipitation experiments, quantitative analysis of BR biosynthetic intermediates reveals that TCP1 promotes BR biosynthesis by directly stimulating the expression of DWF4, possibly thereby leading to the longitudinal elongation of petioles, rosette leaves and inflorescent stems.…”
Section: Developmental Functions Of Tcp Proteinsmentioning
confidence: 99%